Caracterización de dos tipos de Vanilla planifolia - Castillo Martinez, Roberta; Engleman, E. Mark (Instituto de Ecología, A.C., 1993)
In the reproductive state, two kinds of vanilla plants were selected: a) Mansa or Fina and b) Oreja de Burro or Mestiza. Their vegetative and reproductive parts were measured. The flowering periods and number of retained fruits were recorded. The vegetative parts of Oreja de Burro were larger, with a significance of 0.01. The number of flowers per inflorescence is less in Oreja de Burro, and the perianth has a larger yellowish zone. The fruit of Oreja de Burro is larger and its base is more slender than in the Mansa. The periods of abundant flowering were aproximately 20 and 30 days for Mansa and Oreja de Burro, respectively. Between 1.5 and 2.5 months after polinization, Oreja de Burro aborted 74% of its fruits, the harvest was only from 20% of the initial fruit set. As opposed to these results, the Mansa aborted only 3 to 4% per month; the harvest was more than 75% of the initial fruit set. We conclude that Oreja de Burro and Mansa have morphological and phenological characteristics which permit their clear separation.